Comparative Analysis of Lactoferrin Content in Raw Milk from Different Regions and Seasons - ZHOU Shuping, HAN Rongwei, WANG Jiaqi, ZHENG Nan (Shipin Kexue)
In order to analyze the effects of regions and seasons on the lactoferrin content in raw milk produced by healthy dairy cows in the major dairy-producing areas of China and to explore the difference in lactoferrin content in raw milk in China, a total of 164 raw milk samples were collected in four seasons from the six major dairy-producing areas in China and analyzed for their lactoferrin contents by ultra-high performance liquid chromatography (UPLC). The results showed that there was no significant difference in lactoferrin content in raw milk samples from North China, South China, Southwest China, Northeast China, Northwest China, and East China. The lactoferrin content of raw milk collected in autumn and winter was significantly higher than that in spring and summer. This study revealed the regional and seasonal differences in lactoferrin content in raw milk.